Safety and efficacy of sphenopalatine artery ligation in recalcitrant pediatric epistaxis. (August 2019) - D'Oto, Alexandra D.; Cox, Steven; Svider, Peter; Rangarajan, Sanjeet; Sheyn, Anthony
Abstract: Background: Epistaxis is a common cause for emergency department visits for both children and adults. In particular, posterior bleeds can be difficult to identify and treat. In adults, endoscopic sphenopalatine artery (SPA) ligation has been shown to be safe, cost-effective, and curative. Conversely, very few studies have delved into the safety and efficacy of SPA ligation in children. This study aims to evaluate the feasibility of SPA ligation for treatment of recalcitrant epistaxis in children. Methods: A retrospective analysis of outcomes in pediatric patients who underwent SPA ligation at a tertiary academic center was performed. Patients with coagulopathies or other underlying conditions were excluded from the study. Results: Data obtained from 5 patients demonstrated 60% of the population were female, with ages ranging from 2 to 13 years. 7 SPA ligations were performed among the 5 patients, with 3 undergoing unilateral SPA ligation only. The remaining 4 underwent contralateral SPA ligation subsequently. No postoperative complications were observed, and all patients experienced resolution of significant epistaxis. Conclusion: Although additional studies are necessary to further support our findings, SPA ligation in the pediatric population appears to be a safe and effective treatment to control persistent posterior bleeds.